The Importance of the World Heritage Title. The Hungarian World Heritage - Tőzsér, Anett (Acta Carolus Robertus, 2025)
In 1985, Hungary joined the UNESCO World Heritage Convention adopted in 1972. By signing the accession treaty, our nation undertook to protect and preserve the sites on its territory for future generations, and to contribute to the protection of the sites on the World Heritage List as far as possible. Following UNESCO's decision, eight Hungarian sites are currently on the World Heritage List. Seven of the locations were classified as cultural and one as natural. In this study, I examined the process of the creation of the UNESCO World Heritage Convention and the content of the World Heritage Convention with literary sources. In addition, I presented the content of UNESCO's international convention on the preservation of intangible cultural heritage. I also explored the legislative background for World Heritage sites and values in Hungary. The domestic legislation enacted in relation to world heritage sites covers, among other things, the regulation of the exploration, protection, public ownership, sustainable use and management of world heritage sites, the organization of potential world heritage sites in Hungary, and the regulation of the operation of organizations responsible for domestic world heritage sites.
Keywords: world heritage; World Heritage Convention; intangible cultural heritage; Hungarian world heritage sites; legal background